Effect of a Novel Mindfulness Curriculum on Burnout During Pediatric Internship: A Cluster Randomized Clinical Trial. Issue 10 (October 2022) - Fraiman, Yarden S.; Cheston, Christine C.; Cabral, Howard J.; Allen, Celeste; Asnes, Andrea G.; Barrett, Jefferson T.; Batra, Maneesh; Bernstein, William; Bleeker, Tammy; Dietz, Pam M.; Lewis, Joanna; Li, Su-Ting T.; et al.
Abstract : (Abstracted from JAMA Pediatr 2022;176:365–372) Burnout, or the combination of emotional exhaustion (EE), depersonalization, and feelings of helplessness, has an adverse impact on providers and patients across the health system. It has been reported that burnout affects between 39% and 75% of pediatric interns.